Role of Ficus racemosa L. (Moraceae) in Biodiversity Conservation - Sharmila D. Dorage; Jalindarnath G. Bagal (The Bioscan, 2025)
Genus Ficus (Family- Moraceae) is the large and oldest genus present on earth which comprised more than 700 species. It is extremely significant for retaining the biodiversity in tropical and subtropical regions of the world. The Ficus racemosa L. typically contributes to the provision of several ecosystem services in rural settings through plant-organism interactions. Fig wasps have unique mutualistic association with this plant species for pollination and consequently, this plant produced fruit throughout the year. The majority of frugivorous avian and chiropteran species rely on them for a healthy diet, due to the high quantities of rare nutrients found in fig fruits. The diverse forms of organisms that includes, 7 species of aves to 3 species of a mammals from advanced class (frugivorous and insectivorous bats) visited this plant species for food supply and habitation (nesting, roosting, settling, and perching etc.). These animals and birds plays crucial role in the dispersal of tropical seeds. The ripe and unripe fruits, as well as leaves, are used as fodder for domestic live stocks. Humans devour ripened fruits as well as used immature fruits in their savory cuisines. It is popularly used as medicinal plant in ayurveda to treat various ailments. The current study focuses on the scenario of biodiversity conservation by emphasizing the various interactions between Ficus racemosa L. plant and birds, animals, insects and also human beings which can be increase approaches for biodiversity conservation. Keywords Ficus racemosa L., Plant-Organism Interaction, Biodiversity Conservation